OS 19-04 CHRONIC DIURETIC THERAPY DOES NOT IMPAIR THE EFFECTIVENESS OF PATIROMER IN HYPERKALEMIC PATIENTS WITH CKD. (September 2016) - Weir, Matthew; Mayo, Martha; Garza, Dahlia; Arthur, Susan; Berman, Lance; Bushinsky, David; Wilson, Daniel; Epstein, Murray
Abstract : Objective: Diuretics, alone or in combination, are frequently prescribed in chronic kidney disease (CKD) and heart failure (HF) patients to reduce volume, blood pressure, and/or for symptom control. Clinicians may also use them to reduce the risk of hyperkalemia, but high doses of diuretics may lead to adverse events from intravascular volume depletion or gout. Patiromer is a non-absorbed K + -binding polymer recently approved by the FDA for the treatment of hyperkalemia (HK). We compared patiromer's effects in RAASi-treated CKD patients with HK on different types of diuretics to patients not receiving diuretics in the treatment phase of OPAL-HK. Design and Method: CKD patients (n = 243) with baseline serum K + 5.1 to < 6.5 mEq/L on RAASi received patiromer (4.2 or 8.4 g twice daily to start) in the 4-week treatment phase of OPAL-HK. For this post hoc analysis, change in serum-K + from baseline to week 4 was assessed in patients stratified by baseline diuretic use: 1) loop only, 2) thiazide/thiazide-like only, 3) combination of loop and thiazide/thiazide-like, 4) any (alone or in combination), and 5) none. Subjects receiving aldosterone antagonists alone were allocated to the "No Diuretics" group. Results: Across groups, mean (SD) age ranged from 62.9 (10.5) to 65.4 (8.6) years and % male from 51% to 67%. Mean serum K + decreased from baseline at week 4 in all subgroups (Table). Reductions in serum K + did not differ in patients receiving any diuretic vs those not on diuretics. Patiromer was well tolerated; mild-to-moderate constipation was the most common AE (14.4% and 7.6%, respectively, in patients not on diuretics and on any diuretics), with 1 patient in each group discontinuing. Hypokalemia (serum K + < 3.5 mEq/L) was reported in 3.7% and 2.3%, respectively Conclusions: The serum K + -lowering efficacy of patiromer in HK patients was unaffected by concomitant diuretics.